Patient and Professional Constructions of Familial Hypercholesterolaemia and Heart Disease: Testing the Limits of the Geneticisation Thesis - Weiner, Kate (2006)
This thesis provides an empirical investigation of the geneticisation thesis. Geneticisation is one of the most prominent critiques of the social and cultural implications of developments in genetics. It incorporates a set of claims and expectations about the way genetic knowledge and technologies are transforming or will transform ideas about health and illness, and health care practices. This research aims to explore the empirical basis of these claims, by looking at the place of genetic discourses and practices in one specific area. The thesis focuses on familial hypercholesterolaemia (FH), a treatable hereditary cholesterol condition associated with high rates of coronary heart disease (CHD). It asks how much and in what ways patients with FH and professionals involved with the condition construct FH and CHD as genetic conditions.